Government Resource Planning-Based Transformation Strategy for Budget Planning System in Planning Division Directorate General of Sea Transportation - Hari Ryanto Wiyono; Dikky Indrawan; Irman Hermadi (Green Publisher Indonesia, 2025)
The fragmentation of planning and budgeting systems in government institutions poses significant challenges to operational efficiency and strategic decision-making. This research develops a comprehensive transformation strategy for the budget planning system at the Directorate General of Sea Transportation, Ministry of Transportation, Indonesia. Using As-Is Analysis and Soft System Methodology (SSM), the study examines current system conditions and identifies transformation requirements. The analysis reveals critical challenges including the operation of three separate systems (E-Planning, KRISNA, and SAKTI) without integration protocols, dominance of manual processes in budget calculations for 302 work units, and absence of standardized digital infrastructure. Through SSM implementation, two conceptual models were developed addressing digital transformation and system integration requirements. Gap analysis between conceptual models and reality identified deficiencies across six dimensions: stakeholder engagement, system architecture, performance management, technical design, implementation strategy, and risk management. The research proposes Government Resource Planning (GRP) implementation through four integrated strategies: developing integrated system architecture with modular design principles, implementing organizational change management addressing human and institutional factors, establishing interoperability protocols for seamless data exchange, and creating comprehensive evaluation and risk mitigation frameworks. A phased implementation roadmap spanning 18 months provides a pragmatic approach to transformation. This research contributes to digital government literature by demonstrating the effectiveness of combining As-Is Analysis with SSM in addressing complex socio-technical challenges, while offering practical frameworks for government agencies pursuing similar transformations. The findings have significant implications for Indonesia's digital government initiatives and public sector modernization efforts.